Differential equations and mathematical physics : proceedings of the international conference held at the University of Alabama at Birmingham, March 15-21, 1990 - Bennewitz, Christer, 1943- (Mathematics in science and engineering ;, 1992)
Differential equations and mathematical physics : proceedings of the international conference held at the University of Alabama at Birmingham, March 15-21, 1990.